2020
DOI: 10.1183/16000617.0167-2019
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in chronic hypersensitivity pneumonitis

Abstract: Hypersensitivity pneumonitis (HP) is an immunologically mediated lung disease resulting from exposure to inhaled environmental antigens. Prognosis is variable, with a subset of patients developing progressive fibrosis leading to respiratory failure and death. Therefore, there is an urgent need to identify factors which predict prognosis and survival in patients with HP. We undertook a narrative review of existing evidence to identify prognostic factors in patients with chronic HP. Patient demographics, smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 75 publications
0
16
0
1
Order By: Relevance
“…Frequently used prognostic factors in fibrotic ILD include older age, male sex and lower baseline FVC and diffusing capacity of the lung for carbon monoxide (DLCO), which have all been associated with progressive disease in various ILD subtypes. [24][25][26] However, the imperfect predictive ability of these clinical features raises the question of whether additional factors may provide further prognostic information. RF and ACPA presence have previously been associated with increased mortality in RA and RA-ILD, 27,28 but their prognostic impact in other ILD subtypes is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently used prognostic factors in fibrotic ILD include older age, male sex and lower baseline FVC and diffusing capacity of the lung for carbon monoxide (DLCO), which have all been associated with progressive disease in various ILD subtypes. [24][25][26] However, the imperfect predictive ability of these clinical features raises the question of whether additional factors may provide further prognostic information. RF and ACPA presence have previously been associated with increased mortality in RA and RA-ILD, 27,28 but their prognostic impact in other ILD subtypes is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Antigen avoidance is a key aspect of management, however about half of patients with chronic HP do not have identifiable inciting antigen, which is associated with worse prognosis ( 50 ). Other clinical factors associated with worse prognosis include older age, male sex, smoking history, lower baseline FVC or DLCO, and absent lymphocytosis on bronchoalveolar lavage ( 47 , 51 ). In addition to antigen avoidance, corticosteroids and steroid-sparing agents are often used, with limited evidence ( 52 ).…”
Section: Ilds At Risk For a Progressive Fibrosing Phenotypementioning
confidence: 99%
“…It remains unknown why, among such a considerable number of people exposed, only a slight percentage of them become ill, and why the disease may take a chronic form with an unfavourable prognosis [11]. Creamer and Barratt [37] presented a review of the current data concerning prognostic factors of the progression and survival with chronic HP. The researchers reported that older age is associated with increased mortality due to hypersensitivity pneumonitis, similar to COVID-19.…”
Section: Clinical Course Of Hypersensitivity Pneumonitis (Hp)mentioning
confidence: 99%